Relationship between Dairy Product Consumption and Oligospermia; a Case-Control Study - Dizavi, Alireza; Eini-Zinab, Hassan; Hosseini, Jalil; Omidvar, Nasrin; Hosseini, Mohammad Ali (Archives of Men’s Health, 2018)
Introduction: Infertility affects an estimated 15% of couples globally and in Iran, a quarter of Introduction: One of the current debates regarding men’s reproductive health is the declining sperm count and the role of nutritional and environmental factors. This study aims to investigate the association between dairy product consumption and oligozoospermia, sperm count of 5 to 15 million per milliliter of semen, in adult men. Materials and Methods: This age-matched case-control study was conducted on 102 oligozoospermia and 306 healthy men (control group). Both groups were recruited from an infertility clinic in Tehran, the Royan Institute. Dietary intake of subjects was collected using a valid and reliable 168-item food frequency questionnaire. Odds ratios (OR), ex-tracted from conditional logistic regression, were used to compare the occurrence of oligozoospermia by tertiles of dairy intake. Results: After adjusting for potential confounding variables, the high intake of low-fat dairy products was inversely associated with the risk of oligozoospermia (OR: 0.48; 95%CI: 0.24 – 0.95), (P =0.046). The higher intake of high–fat dairy products [(OR: 2.44; 95%CI: 1.26 – 4.73), (P =0.008)], high–fat milk [(OR: 2.16; 95%CI: 1.09 – 4.30), (P =0.043)], and ice creams [(OR: 2.37; 95%CI: 1.25 – 4.50), (P =0.008)] were also positively associated with oligozo-ospermia. Conclusion: The high intake of low–fat dairy foods seems to have a protective effect on oligozoospermia. Higher intake of high – fat dairy products, high– fat milk, and ice creams were associated with an increased risk of oligozo-ospermia.